1978
DOI: 10.1128/aac.13.4.570
|View full text |Cite
|
Sign up to set email alerts
|

New In Vitro Model to Study the Effect of Antibiotic Concentration and Rate of Elimination on Antibacterial Activity

Abstract: A new apparatus is described which serves to investigate the in vitro antibacterial activity of antibiotics as a function of different concentration time curves. The apparatus can be adjusted to simulate the biexponential serum level curves observed in vivo after oral or intramuscular administration. Preliminary studies were carried out with a cephalosporin derivative, cefazolin, against Escherichia coli and Klebsiella sp. strains simulating initial concentrations of 5, 10, and 20 pug/ml that decreased exponen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(114 citation statements)
references
References 6 publications
3
110
0
1
Order By: Relevance
“…For the experimental evaluation of the PK-PD relationship of ciprofloxacin against E. coli, a slightly modified in vitro method, that of Grasso et al (9), was used. The experimental setting consisted of a central compartment without a separating membrane (calibrated Erlenmeyer flasks with a total volume of 300 ml and containing 100 ml of medium) into which the antibiotic is pumped via programmable pumps until the maximum serum concentration to be simulated is reached.…”
Section: Methodsmentioning
confidence: 99%
“…For the experimental evaluation of the PK-PD relationship of ciprofloxacin against E. coli, a slightly modified in vitro method, that of Grasso et al (9), was used. The experimental setting consisted of a central compartment without a separating membrane (calibrated Erlenmeyer flasks with a total volume of 300 ml and containing 100 ml of medium) into which the antibiotic is pumped via programmable pumps until the maximum serum concentration to be simulated is reached.…”
Section: Methodsmentioning
confidence: 99%
“…The main limitation of this model was that the volume in the flask increased throughout the experiment, diluting also the inoculum and posing practical problems for large dilutions. A one compartment open model that used a system consisting of two flasks interconnected by a peristaltic pump to simulate first-order kinetics was developed by Grasso et al (53). Sterile broth was pumped from the diluent reservoir flask to the flask containing the bacterial culture and the antibiotic.…”
Section: Models With Variable Antibiotic Concentrationsmentioning
confidence: 99%
“…Skopnik compared two groups of neonates who received once-and twice-daily doses of gentamicin and found that the once-daily group did better regarding efficacy and toxicity (21). High peak concentration of aminoglycoside is the major determinant of bacterial killing rather than the minimum inhibitory concentration of the antibiotic (23,24). The target peak concentration of gentamicin is 4-12 µg/mL (25) but 29% (17/59) of the cases in this study had higher peak values (range 12.1-20.6 µg/ mL).…”
Section: Discussionmentioning
confidence: 99%